PERBANDINGAN PERFORMA PROTOKOL COAP DAN HTTP PADA MIKROKONTROLER ESP32 SEBAGAI PERANGKAT IOT PEMANTAU KUALITAS UDARA - Wijayanto, Micko; Muttaqin, Adharul; Razak, Angger Abdul (Jurnal Mahasiswa TEUB, 2024)
The development of the Internet of Things (IoT) is driving transformation in various sectors of life. One important aspect of IoT technology is data communication, which has various solutions, including the Internet. With a variety of internet protocol solutions available, appropriate protocol recommendations are needed for IoT needs, such as CoAP or HTTP. This research compares the performance of these two protocols using an ESP32 Microcontroller integrated with MQ7 and DHT11 sensors for air quality monitoring. Performance assessments include data communication network, power consumption, and memory requirements. Implementing the CoAP Protocol requires configuration so that data packets can capture tokens provided by clients. Data communication analysis, using Wireshark software, shows that the average delay of CoAP is 80% higher compared to HTTP, and the average power consumed by CoAP is also 4% greater. However, the average throughput measured is 27% higher in HTTP compared to CoAP, and CoAP's storage efficiency is also 3% better. Meanwhile, both protocols have insignificant differences in data delivery reliability and dynamic memory usage. Keywords: Internet of Things, Microcontroller ESP32, CoAP, HTTP, Performance Comparasion